Demand or Supply? Price Adjustment during the Covid-19 Pandemic - Almut Balleer; Sebastian Link; Manuel Menkhoff; Peter Zorn (Center for Economic Studies and Ifo Institute (CESifo), 2020)
We study price-setting behavior in German firm-level survey data to infer the relative importance of supply and demand during the Covid-19 pandemic. Supply and demand forces coexist, but demand shortages dominate in the short run. A reported negative impact of Covid-19 on current business is associated with a rise in the probability to decrease prices up to eleven percentage points. These results imply a role for aggregate demand stabilization policy to buffer the economic consequences of Covid-19 while containing the pandemic.
Keywords: E31; E32; H50; E60; D22; 330; producer price setting; supply; demand; Covid-19; fiscal policy